An Assessment of Communication about Family Planning on Desired Fertility: The Case of Rwanda - Gasafari, Willy; Dungumaro, Esther (Tanzania Journal for Population studies and Development, 2014)
Despite the recognition of the importance of spousal communication in family planning programs, it remains a challenge to many couples in sub Saharan Africa. This paper uses the 2000 Rwanda Demographic and Health Survey (RDHS) to assess spousal communication about family planning on desired fertility. Analysis is done on married people aged 15–49 years. Results indicate that communication about family planning is a significant covariate of the desire to have no more children. The direction of causation in this relationship is plausibly two-way: occurring when already established fertility desires are articulated to the partner, and when a discussion of advantages of child spacing or birth limitation is translated into lower fertility desires, for one or both partners. Results show that fertility desire of wives and husbands are shaped by the partner’s desire, whether or not these are explicitly communicated. Multivariate results show that current age has a small but highly significant effect on the desire for additional children among both men and women. Older men and women are more likely to want no more children. Urban residence is significantly related to desired fertility, indicating the overall level of wanting no more children in urban areas than in rural areas. The paper recommends various alternatives to encourage spousal communication about family planning, taking into consideration various challenges that prevail in African societies.